Taxing powers of state and local government (OECD ParisFR, 1999)
Contains a description of fiscal relations in most of the nineteen OECD countries and provides a set of detailed tables for each country, with revenues split by: level of sub-central government; OECD classification of taxes; and, category of tax autonomy following the framework developed by the Working Party of Tax Policy Analysis and Tax Statistics.
Keywords: TAXATION